Bed-trick and forced marriages. Shakespeare’s distortion of romantic comedy motifs in Measure for Measure - Frédérique Fouassier (Sillages Critiques)
Although Measure for Measure ends with marriages and thus looks like a comedy, its ending leaves the audience unsettled. The Problem Plays in general, and Measure for Measure in particular, contrast with Shakespeare’s earlier, “romantic” comedies although one finds in it some of their features and patterns. But these motifs are treated in an ironical way and seen through a distorting mirror. The marriage bed to which couples withdraw at the end of romantic comedies here takes the shape of the morally puzzling bed-trick, and marriage itself, which is conventionally the emblem of fulfilment and embodies a promise of happiness and harmony, is marked with negative connotations. One of the most blatant consequences of the distortion of romantic comedy motifs in Measure for Measure is the disempowerment of female characters: at the conclusion of the play, they are violently levelled out, at the lowest possible level: they all become Kate Keepdowns.